Pathogenetic Factors Contributing to the Development of Delayed Complications of Acute Destructive Pancreatitis - A. V. Ershov; V. T. Dolgikh; O. V. Korpacheva; V. V. Rusakov; N. N. Nikolaev; S. V. Palianov (Общая реаниматология)
Purpose. To evaluate pathogenic factors contributing to the development of delayed complications of newly diagnosed acute destructive pancreatitis (ADP).Materials and methods. A comprehensive examination, treatment and 5-year follow%up of 83 patients who underwent the first attack of ADP have been conducted. The day of admission to the hospital, 24 hours from the beginning of the intensive care, and Days 3 and 5 after the attack were selected as the timepoints of the study. Complete diagnostic procedures were performed once every six months after hospitalization for five years. The patients were followed%up every month. Depending on the further progression of ADP, the patients were divided into four groups. Group I included 27 patients with acute pancreatitis which evolved into pancreatic pseudocysts.Group II (n=43) was comprized of the patients with chronic pancreatitis; group III (n=8) included the patients who presented no pathological processes associated with structural and functional pancreatic changes over the next 5 years; and group IV (n=5) included the patients with pancreatogenic diabetes mellitus.Results. The study confirmed the role of autoimmune mechanisms and abnormal foci localization in pancreas in the development of pancreatogenic diabetes mellitus, contribution of inflammation to formation of post-necrotic pancreatic pseudocysts, as well as the significance of the patient compliance for development of chronic pancreatitis with extensive pancreatic lesions.Conclusion. Statistical analysis of the long-term monitoring of patients allowed to set the odds ratio evolution acute pancreatitis depending on its initial characteristics. At the same time we take into account the parameters and interpretation of the study which is possible in the first few days hospitalization.